PELANGGARAN KEWAJIBAN PENDAFTARAN SERTIFIKAT HALAL: Dapatkah Dibuat Sanksi? - Nasyi’ah, Iffaty (Jurisdictie: Jurnal Hukum dan Syariah, 2018)
The number of businessmen who have not yet registered for halal certificate grabs government’s attention. This is reflected in the Article 4 about Halal Product Warranty (Jaminan Produk Halal/JPH). The infraction against that article has no juridical implication, either administratively or criminally. The inconsistency of this article encourages researcher to seek for answers on two issues: can the infraction of article 4 be judged? Which kind of sanction is appropriate as the juridical consequence of the aforementioned article? The article is a normative research and uses legislation and conceptual approaches. Using the individual-liberalistic and strafrecht’s ordenings theories, the researcher assumes that infraction against Article 4 of JPH Law is still possible. The reason is that this article does not have a particular status of infraction; either it is civil, administrative, or criminal. This JPH law should be revised by adding strict sanctions, in both, the article itself and the chapter on criminal provision. Criminal sanctions that can be given are confinement and/or fine payment.